Mewujudkan Karakter Pancasila melalui Projek Gaya Hidup Berkelanjutan: Analisis Evaluatif dengan Model CIPP di Fase C - Beni Yuli Prastowo; Herwin Herwin (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
This study aims to evaluate the implementation of the Pancasila Student Profile Strengthening Project (P5) with the theme “Sustainable Lifestyle” in Phase C (Grade V) at SDN Kaligatuk, using the CIPP evaluation model (Context, Input, Process, Product). This research employed a descriptive evaluative approach, involving one principal, one teacher, and sixteen students as participants. Data were collected through questionnaires, observations, and in-depth interviews, and analyzed using descriptive quantitative and interpretive qualitative techniques. The findings reveal that the implementation of the P5 project at SDN Kaligatuk is categorized as very good. In terms of context, the objectives and relevance of the program align well with students’ character development needs. The input component shows adequate teacher training and sufficient facilities supporting project implementation. The process dimension demonstrates active student participation in collaborative and reflective learning activities, although students’ confidence in expressing opinions requires further development. The product component shows that the project yields tangible outcomes and positive behavioral changes reflecting Pancasila values such as responsibility, cooperation, and environmental awareness. This study concludes that the CIPP model is effective for evaluating P5 program.